การรักษาโรคนิ้วล็อกด้วยอุปกรณ์ดามนิ้ว - ทองใบ, รัตติกร; วงค์ษา, ญาณินี (Siriraj Medical Bulletin, 2018)
Trigger finger as stenosing tenovaginitis is common disease that cause pain in the hand, can be found in both adult and pediatric population. It affects woman more often than men and most commonly affected digit being the thumb. Trigger finger symptoms can include pain, clicking, catching and loss of motion of the affected finger. There are various method of treatment including conservative treatment with Trigger finger splint. Trigger finger splint is appropriate for patient with early trigger finger and pediatric patients. It was efficient in shortening time for symptom relief, reduce the cost of treatment and did not any complication. The patient can return to the daily life faster.